2011
DOI: 10.1016/j.ultsonch.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid under ultrasonic irradiation towards a facile synthesis of pyrazolone derivatives

Abstract: Ionic liquid [HMIM]HSO(4) was found to be an efficient catalyst for the synthesis of 4-[(5-hydroxy-3-methyl-1-phenyl-1H-pyrazol-4-yl)-phenyl-methyl]-5-methyl-2-phen-yl-1,2-dihydro-pyrazol-3-ones through the condensation reaction of arylaldehydes and 3-methyl-1-phenyl-5-pyrazolone under ultrasonic irradiation at room temperature. The present methodology offers several advantages such as excellent yields, simple procedure and mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…In recent years, ILs have been found to be excellent solvents for dissolution of nucleosides (Uzagare et al, 2003;Kumar et al, 2007; Moniruzzaman et al, 2010c). This finding opens the door to using ILs as reaction media for synthesis of nucleoside analogs with many advantages over conventional solvents (Uzagare et al, 2003;Malhotra, 2008, 2009;Zhang et al, 2009;Zang et al, 2011). Uzagare et al (2003) have reported on the acylation of 3Ј-and 5Ј-functional groups of sugars and NH 2 of base of 2Ј-deoxynucleosides in IL [MOemim][OMs] with different acylating agents including acetic anhydride, benzoyl chloride and isobutyryl chloride (see Figure 3).…”
Section: Synthesis Of Drug Compounds In Ionic Liquids Mediamentioning
confidence: 99%
“…In recent years, ILs have been found to be excellent solvents for dissolution of nucleosides (Uzagare et al, 2003;Kumar et al, 2007; Moniruzzaman et al, 2010c). This finding opens the door to using ILs as reaction media for synthesis of nucleoside analogs with many advantages over conventional solvents (Uzagare et al, 2003;Malhotra, 2008, 2009;Zhang et al, 2009;Zang et al, 2011). Uzagare et al (2003) have reported on the acylation of 3Ј-and 5Ј-functional groups of sugars and NH 2 of base of 2Ј-deoxynucleosides in IL [MOemim][OMs] with different acylating agents including acetic anhydride, benzoyl chloride and isobutyryl chloride (see Figure 3).…”
Section: Synthesis Of Drug Compounds In Ionic Liquids Mediamentioning
confidence: 99%
“…These directly help in shortening the time span of reactions and increasing the yield of products [56]. Moreover a large number of reactions can be carried out in shorter reaction time, higher yield through milder reaction conditions under Ultra sound Irradiation [57]- [59]. Many homogeneous and heterogeneous reactions can be conducted smoothly by sonication to provide improved yields and increased selectivity [60].…”
Section: Introductionmentioning
confidence: 99%
“…Compounds with pyrazolemoieties as nitrogen-containing heterocyclic systems have received attention owing to their diverse biological activities. These include anti-inflammatory, antipyretic and analgesic activities, uses as bactericides and fungicides, and promising inhibitory activity against monoamine oxidase for the treatment of Parkinson's and Alzheimer's diseases [1,4,[12][13][14]. More specifically, 4,4 1 -(arylmethylene)bis(3-methyl-1-phenyl-1H-pyrazol-5-ol)s is an important class of pyrazolones used as anti-inflammatories [15], antipyretics, gastric secretion stimulatories [16], antidepressants [17], and antibacterial and anti-filaria agents [11,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%